Factors Associated with Stunting in Children Under Five: A Cross-Sectional Study from Ritaebang Health Center, West Solor, East Flores, Indonesia - Marina A.B Ndetu; Pius Weraman; Petrus Romeo (Journal of Health Promotion and Behavior, 2023)
Background: Stunting in children under five years of age is a global nutritional problem. World Health Organization (WHO) puts Indonesia as the third country with the highest cases in Asia. Prevalence of stunting in children under five years of age in East Nusa Tenggara touches 40.3%, the highest compared to other provinces in Indonesia. The study aims to discover factors associated with stunting incidences in children under five years of age in the working area of Ritaebang Community Health Center, West Solor, East Flores.Subjects and Method: This cross-sectional study was conducted in the working area of Ritaebang Community Health Center, West Solor, East Flores during the month of June – July 2022. A total of 70 children under five years of age were selected by using random sampling. The dependent variables were birth weight, consumption pattern, clean water availability, maternal education, number of family members, and family income. The independent variable was stunting children under five years of age. The data were collected by using questionnaires, and analyzed by using SPSS.Results: The stunting incidences in children under five years of age were significantly associated with exclusive breastfeeding (OR= 3.91; p= 0.046), consumption pattern (OR= 19.63; p<0.001), the availability of clean water (OR= 6.37; p= 0.001), maternal education, (OR= 3.14; p= 0.033), number of family members (OR= 6.71; p= 0.007), and family income (OR= 12.25; p= 0.008), and were also associated with birth weight (OR= 3.61; p= 0.214), however it was not statistically significant.Conclusion: Stunting incidences is associated with birth weight, breastfeeding, consumption pattern, clean water availability, maternal education, number of family members, and family income.Keywords: stunting, birth weight, clean water, environment.Correspondence:Marina A.B Ndetu. Public Health Department, Public Health Faculty, Universitas Nusa Cendana. Jl. Adi Sucipto Penfui, Penfui, Maulafa, Kupang, East Nusa Tenggara. 85001. Email: Marinandetu12@gmail.com piusweraman@yahoo.com.Journal of Health Promotion and Behavior (2023), 08(01): 1-7DOI: https://doi.org/10.26911/thejhpb.2023.08.01.01